PERANCANGAN SISTEM INFORMASI PARIWISATA DI KABUPATEN SUKABUMI BERBASIS WEB - Nopita, (2021)
Referring to Law Number 22 Year 1999, which regulates the authorities and obligations of the autonomous region to regulate and manage government affairs and the interests of the local community. This is benefited by the tourism office as the authority in promoting tourism in Sukabumi Regency in the technology sector which is expected to reduce the costs of the tourism office in promoting tourism information. This research uses the waterfall method with the aim of creating a Web-based Design of a Tourism Information System in Sukabumi Regency, as a promotional media in the form of superior tourism information, lodging, restaurants, traditional culinary, traditional arts, and creative industries which visitors will be diverted to the Dekranasda website link. ., and this study uses the PIECES method as problem identification. The results of this research are in the form of a web application that can be used by visitors and the tourism office.